Peningkatan Aktivitas Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SD Muhammadiyah 3 Padangsidimpuan - Siregar, Hendri; Dalimunthe, Efrida Mandasari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The purpose of this study was to describe the efforts made by teachers to increase student activity in Islamic Religious Education subjects at SD Muhammadiyah 3 Padangsidimpuan, therefore, this study used descriptive qualitative research methods, meaning that the data obtained from the field were described with the data obtained explained in accordance with what happens in the field. Sources of data in this study from primary sources which became the first source either from individuals or individuals such as the results of interviews. The sources of this study were 2 teachers of Islamic Religious Education and fifth grade students at SD Muhammadiyah 3 Padangsidimpuan, so primary data was collected using research and information sources and questionnaires. The instruments used in this study were observation and interviews. The results of this study found several efforts made by PAI teachers in increasing student learning activities in the classroom.